Proteomic analysis of Oesophagostomum dentatum (Nematoda) during larval transition, and the effects of hydrolase inhibitors on development. - Martina Ondrovics (Public Library of Science (PLoS), 2013)
In this study, in vitro drug testing was combined with proteomic and bioinformatic analyses to identify and characterize proteins involved in larval development of Oesophagostomum dentatum, an economically important parasitic nematode. Four hydrolase inhibitors ο-phenanthroline, sodium fluoride, iodoacetamide and 1,2-epoxy-3-(pnitrophenoxy)-propane (EPNP) significantly inhibited (≥90%) larval development. Comparison of the proteomic profiles of the development-inhibited larvae with those of uninhibited control larvae using two-dimensional gel electrophoresis, and subsequent MALDI-TOF mass spectrometric analysis identified a down-regulation of 12 proteins inferred to be involved in various larval developmental processes, including post-embryonic development and growth. Furthermore, three proteins (i.e. intermediate filament protein B, tropomyosin and peptidyl-prolyl cis-trans isomerase) inferred to be involved in the moulting process were down-regulated in moulting- and development-inhibited O. dentatum larvae. This first proteomic map of O. dentatum larvae provides insights in the protein profile of larval development in this parasitic nematode, and significantly improves our understanding of the fundamental biology of its development. The results and the approach used might assist in developing new interventions against parasitic nematodes by blocking or disrupting their key biological pathways.